Gambaran Status Mental Pasien SkizofreniaDi Rumah Sakit Jiwa DaerahSoedjarwadi Klaten - Mida, Yuniar Fusfita, Arum Pratiwi, S.Kp., M.Kes (2017)
Schizophrenia is a mental disorder that show impaired in cognitive function (thinking) in the form of disorganization, Schizophrenia strikes at the productive age and is a psychiatric disorder most dominating compared to other mental disorders. Assessment on the mental status of patients with Schizophrenia conducted to determine how the level and function of a person's soul that contain aspects of intelligence, affective, emotions, attitudes, interests and psychomotor personality. Treatment of patients with Schizophrenia that do continuously is very important to control the symptoms of Schizophrenia and preventing relapse of Schizophrenia. Control of the patient's mental status is performed to determine whether the treatment has been carried out successfully or not. The purpose of this study is to describe the mental status patients with Schizophrenia at the Soedjarwadi Psychiatric Hospital Klaten. This research is a descriptive with quantitative approach. The study population was 748 patients with Schizophrenia. Sample of this research are 88 patients were determined using proportional random sampling method. Collecting data using observation and interview sheet, andthe data analysis using descriptive test. Conclusion of this study is an overview of mental status patients with Schizophreniain Soedjarwadi Psychiatric Hospital Klaten mostly is maladaptive.